2004
DOI: 10.1128/jb.186.18.6298-6305.2004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Global Changes in Gene Expression during Temperature Transition in Yersinia pestis

Abstract: DNA microarrays encompassing the entire genome of Yersinia pestis were used to characterize global regulatory changes during steady-state vegetative growth occurring after shift from 26 to 37°C in the presence and absence of Ca 2؉ . Transcriptional profiles revealed that 51, 4, and 13 respective genes and open reading frames (ORFs) on pCD, pPCP, and pMT were thermoinduced and that the majority of these genes carried by pCD were downregulated by Ca 2؉ . In contrast, Ca 2؉ had little effect on chromosomal genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
166
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(185 citation statements)
references
References 38 publications
(20 reference statements)
17
166
0
2
Order By: Relevance
“…14 A few groups have used whole-genome DNA microarray analysis to investigate transcriptional regulation upon the upshift of growth temperature from 26ºC to 37ºC in a chemically defined medium with or without 2.5 mM CaCl. 13,14 Genes which were upregulated quickly after the shift to 37ºC may be valid Y. pestis virulence factor candidates, since early changes in transcriptional expression due to temperature shift probably reflect adaptation to the host rather than changes solely integral to the onset of bacteriostasis. Transcriptional profiles reported by Motin et al 13 revealed thermal induction of 51, 4 and 13 genes or open reading frames on pCD1, pPCP and pMT, respectively.…”
Section: Comparative Genomic Studiesmentioning
confidence: 99%
“…14 A few groups have used whole-genome DNA microarray analysis to investigate transcriptional regulation upon the upshift of growth temperature from 26ºC to 37ºC in a chemically defined medium with or without 2.5 mM CaCl. 13,14 Genes which were upregulated quickly after the shift to 37ºC may be valid Y. pestis virulence factor candidates, since early changes in transcriptional expression due to temperature shift probably reflect adaptation to the host rather than changes solely integral to the onset of bacteriostasis. Transcriptional profiles reported by Motin et al 13 revealed thermal induction of 51, 4 and 13 genes or open reading frames on pCD1, pPCP and pMT, respectively.…”
Section: Comparative Genomic Studiesmentioning
confidence: 99%
“…We specifically targeted proteins encoded by genes implicated in virulence for which there was little or no functional annotation. Expression array experiments with Y. pestis, the etiological agent of bubonic plague, identified a large number of genes that are upregulated in host-mimetic conditions [43]. More than 30% of the implicated genes were annotated as putative or conserved hypothetical, here we will discuss our efforts to characterize one protein, whose gene was annotated as hypothetical conserved protein.…”
Section: The Potential For Mutagen Research At a Structural Genomics mentioning
confidence: 99%
“…The gene with locus tag YPO0407 is upregulated in host-mimetic conditions [43] and was annotated as a hypothetical conserved protein. Starting with only the gene expression data and the annotated sequence, we targeted the protein encoded by YPO0407 for expression and structure determination.…”
Section: The Potential For Mutagen Research At a Structural Genomics mentioning
confidence: 99%
“…[2] Furthermore, Y. pestis gene expression array studies carried out at LLNL have established a correlation between expression of known virulence factors and genes involved in processing of the AI-2 quorum sensing signal. [6] Scope This was a basic research project that was intended to provide new insights into bacterial intercellular communication and how it is used to regulate virulence in Y. pestis. It is known that many bacteria use intercellular signaling molecules to orchestrate gene expression and cellular function.…”
Section: Motivationmentioning
confidence: 99%